Montreal (Annual) Paper - The Use of Producer-Gas for Drying and Roasting Ore at the Lixiviation-Mill of the Holden Smelting and Milling Co., Aspen, Colorado - Willard S. Morse (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1893)
The ores of the district are treated at this mill by the lixiviation process, consisting of drying, crushing, chloridizing-roasting and lixiviation by hyposulphite and Russell solutions. Gas is used as fuel for both drying and roasting, The gas-plant consists of two- Taylor revolving-bottom gas-producers, one 6 feet in diameter for the ore-dryers, the other 7 feet in diameter for the Stetefeldt furnace. The producers were made by Messrs. R. D. Wood & Co., Philadelphia, who also furnished the